Procedimentos administrativos extrajudiciais do Ministério Público: estudo comparado entre as experiências no Brasil e Canadá para proteção de grupos vulneráveis - Ribeiro, Evandro de Aguiar (2024)
The Brazilian Amazon Region serves as the backdrop for an enduring model of development and occupation, leading to ongoing conflicts between various social and economic actors. The State of Pará's Public Prosecutor's Office (MP) emerges as a driver of public policies, collaborating with diverse state and non-state entities. Utilizing both judicial and extrajudicial tools, the MP resolves conflicts among stakeholders, including transnational corporations and traditional populations. This dissertation explores the historical context of Amazonian development, highlighting the impact of major projects on vulnerable communities. It also examines the MP's role in defending human rights, its interactions with other oversight bodies, and implications for integrity and compliance, emphasizing the extrajudicial aspect in rights protection. The study analyzes MP procedural norms, revealing structural challenges, inefficiencies in oversight bodies, and a workload burden, posing challenges to fulfilling its constitutional mission. Employing a documentary method, the research identifies the Amazon Region as a hub for significant economic projects, often led by transnational corporations. A regulatory gap exists for holding these entities accountable in their home countries for rights violations in the areas of operation, impacting the efficacy of the Brazilian MP. The research concludes by engaging in a comparative legal dialogue between Brazil and Canada, focusing on MP models and rights protection entities. Differences between the two countries are highlighted, exploring potential consequences for safeguarding vulnerable populations, particularly in holding Canadian extractive transnational corporations accountable beyond their domestic borders, such as in the Amazon Region